Evaluation of the Implementation of Patient Safety Culture by Medical Personnel at the Amanah Jatisari Karawang Clinic - Jardinia Dian Fatimah; Nining Handayani; Yani Restiani Widjaja (Research of Service Administration Health and Sains Healthys, 2025)
Introduction: Patient safety culture is a vital element in healthcare systems that aims to minimize incident risks and improve service quality. Amanah Jatisari Clinic, as a primary healthcare facility preparing for accreditation, requires an evaluation of the implementation of safety culture by medical personnel. Methods: This study applied a descriptive qualitative method with a case study design. Data were collected through in-depth interviews, non-participatory observations, and document analysis involving 12 healthcare workers including doctors, nurses, pharmacists, and midwives. The research instrument was based on the Hospital Survey on Patient Safety Culture (HSOPSC), and data were analyzed using descriptive and SWOT approaches. Results: The findings indicated that healthcare workers had a generally good perception of patient safety culture, particularly in openness and teamwork dimensions. However, the implementation of reporting and just culture was still suboptimal. Supporting factors included managerial commitment, internal training, and effective communication. Barriers involved staff shortages, high workload, and fear of sanctions. Discussion: SWOT analysis led to several strategic recommendations such as enhancing staff-awareness-based training, developing non-punitive reporting systems, and implementing consistent managerial policies. These results are expected to serve as a basis for continuous improvement of the patient safety culture system in primary healthcare services.